Types Of Conversation In The Movie The Intern - Rian Marianto (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
I am interested in this study “Types of Conversation in the Movie The Intern” because I want to learn about how people interact and communicate in the workplace. The way people use language as their media and from that I am interested to know about how an employee communicate with other employees and how they communicate with their boss. Of course, on the contrary, I also interested to learn how a boss communicate to their employees. In this study I took theory of social situation of language use as my theory and I focus on interactional and transactional conversation analysis. The social situation of language use based on the participants, locale or setting, topics and function. I choose those theories because it is related to my study and it help me to understand about the social situation of language use. Hopefully, this study will help me and other people to understand about how to interact and communicate with fellow partners and the boss in the workplace.Keywords: Analysis, conversation, interactional conversation, transactional conversation, and situation